PENGARUH PAJAK REKLAME TERHADAP PAD DAN PAJAK DAERAH KABUPATEN/KOTA DI JAWA TENGAH TAHUN 2010-2013 - Tikaninda Kumaladewi, 10.05.52.0191; Setyowati, Widhy (Students Journal of Accounting and Banking, 2014)
This study aims to examine and analyze the effect of Advertising Tax,PAD and Tax District / town in Central Java from 2010 to 2013. The population in this study is a local government district / town in Central Java province, amounting to 35. Data analyzed in this paper is a secondary data with census method derived from documents district budget realization report / town in Central Java province obtained from the Site Director General Equilibrium Local Government Finance on the Internet (www.djpk.depkeu.go.id). From this budget realization report obtained data on the number of realizations Advertisement Tax, Revenue (PAD) and Local Taxes in 2010 and 2013.Teknik data analysis used is multiple linear regression analysis. Based on the test results can be result that advertisement tax positive effect on local revenues, the higher the received advertisement tax, regional income will also increase. Advertisement tax positive effect on local taxes, the higher the received advertisement tax, local tax will also increase. Keywords: Advertising Tax, revenue and Local Tax